An investigation of the effective use of information and communication technologies (ICT) for primary school teachers in the transfer of knowledge - Ntombovuyo, Klaas (Stellenbosch : University of Stellenbosch, 2006)
Thesis (MPhil (Information Science))--University of Stellenbosch, 2006.